A STUDY ON THE CORRELATION BETWEEN STUDENTS’ ACHIEVEMENT MOTIVATION AND STUDENTS’ ACHIEVEMENT IN LEARNING ENGLISH AT GRADE TEN OF SMA N 1 SAWAN - ., Ni Luh Anggun Wisma Yanthi; ., Prof. Dr.I Ketut Seken,MA; ., Dewa Ayu Eka Agustini, S.Pd., M.S. (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Penelitian ini bertujuan untuk mengetahui hubungan yang signifikan antara motivasi berprestasi dan prestasi belajar siswa. 123 siswa di kelas X SMA N 1 Sawan dipilih sebagai sampel melalui Simple Random Sampling. Kuesioner motivasi berprestasi dan laporan guru yang terkait dengan hasil prestasi belajar siswa digunakan untuk mengumpulkan dan mendapatkan data untuk penelitian ini. Teknik analisis yang digunakan dalam penelitian ini adalah metode statistik yang berarti bahwa data dianalisis secara kuantitatif, deskriptif dan inferensial. Penelitian ini menemukan bahwa ada hubungan yang signifikan antara motivasi berprestasi dan prestasi belajar siswa. Diketahui bahwa nilai R sebesar 0.89 (R kuadrat = 79.1) .Ini berarti bahwa kekuatan hubungan antara motivasi berprestasi dan Belajar Bahasa Inggris sebesar 0.89. Hal ini menunjukkan ada korelasi yang sangat kuat antara motivasi berprestasi dan prestasi belajar siswa. Kata Kunci : motivasi berprestasi dan hasil belajar This study aimed at finding out whether there is a significant correlation between students’ achievement motivation and students’ learning achievement. A number of 123 students at tenth grade of SMA N 1 Sawan was chosen as the sample through Simple Random Sampling. Achievement motivation questionnaire and teachers’ report that related to students’ learning achievement were used in collecting the intended data in this study. The technique of analysis used in this research was a statistical method which means that the data were analyzed quantitatively, descriptive and inferential statistic methods. This study discovered that there was a significant correlation between students’ achievement motivation and students’ learning achievement. This was found with R value of 0.89 (R square = 79.1). It means that the power of correlation between motivation and achievement in English learning was 0.89. It indicates there was a very strong correlation between students’ achievement motivation and students’ learning achievement.keyword : Achievement motivation and learning achievement